Volume 4B: Combustion, Fuels and Emissions 2015
DOI: 10.1115/gt2015-43433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fuel Characteristics in a Correlation to Predict Lean Blowout of Bluff-Body Stabilized Flames

Abstract: This study employed experimental data collected at the Air Force Research Laboratory (AFRL) as well as data from a review of past literature to develop a correlation for predicting lean blowout through the use of a least-squares curve-fit method. Combining data from the literature with data from AFRL allowed significant variations within the dataset with regard to velocity, flameholder diameter and shape, pressure, temperature, and fuel. Gaseous, single-component fuels as well as multi-component jet fuels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Figure 7(b)). Huelskamp et al 70 have recently shown for a dataset of bluff-body stabilised prevaporised flames that ignition delay times provide an adequate representation of chemical time scale and correlate well with the equivalence ratio at lean blowout.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7(b)). Huelskamp et al 70 have recently shown for a dataset of bluff-body stabilised prevaporised flames that ignition delay times provide an adequate representation of chemical time scale and correlate well with the equivalence ratio at lean blowout.…”
Section: Discussionmentioning
confidence: 99%
“…6(b)). Huelskamp et al [56] have recently shown for a dataset of bluff-body stabilized prevaporized flames that ignition delay times provide an adequate representation of the chemical time scale and correlate well with the equivalence ratio at lean blowout.…”
Section: Discussionmentioning
confidence: 99%
“…The LBO prediction on gas turbine combustor based on correlation has been suggested by many researchers (Jarymowycz and Mellor, 1986;Xie et al, 2012;Huelskamp et al, 2015;Hu et al, 2015;Lei et al, 2021). Jarymowycz and Mellor (1986) developed a correlation to predict LBO in an annular combustor.…”
Section: Introductionmentioning
confidence: 99%